Development of Tutorial Learning Videos on Physical Education Subjects, Football Material in Class VIII SMP - Putra, Donal Andika; Zuliarni, Zuliarni; Yeni, Fetri; Rahmi, Ulfia (JUPE : Jurnal Pendidikan Mandala, 2023)
The development of this learning video media was carried out as an effort to solve student learning problems. This learning media can be used as an alternative to reduce problems in learning. This research aims to produce products for class VIII physical education subjects and determine the quality, validity and practicality of the products developed so that they are suitable for use. This type of research is development research, known as Research and Development (R&D), using the ADDIE development model. The development procedure in this research consists of 4 stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The product validity test was carried out by 3 validators, namely 1 material expert validator and 2 media expert validators. The practicality test was carried out on 15 class VIII students at SMP Angkasa Lanud Sutan Sjahrir Padang. The development of learning video media using the Kinemaster application for Physical Education subjects for class VIII SMP has been carried out in accordance with development procedures which produce learning media in video form. This product has gone through the validation stage. Based on the results of the material validation assessment from the physical education teacher at Angkasa Lanud Padang Middle School and media validation, namely the Curriculum and Education Technology lecturer, the validation results from media expert I have been categorized as "very valid" with an average of 4.94 and the results from media expert II were categorized as "very valid" with an average of 4.64. Meanwhile, the final validation results from material experts were categorized as "very suitable" with an average of 4.75. The practicality test results for learning media products averaged 4.64 in the "Very Practical" category. Based on these results, it can be concluded that the learning video media using the Kinemaster application in Physical Education subjects is declared to be very valid and very practical.